Sales and Distribution Strategies of Organic Beauty Products in India: A Systematic Literature Review Using PRISMA - Savitha.N. L; Dr. Rekha Gothe; Dr. Madhura R; Dr. Vinod Krishna M. U (The Bioscan, 2025)
In summary, this systematic literature review underscores the relative scarcity of research on organic beauty products globally. By employing the PRISMA methodology, the study provided a meticulous examination of current trends and the state of sales and distribution strategies within this domain, drawing from twenty carefully selected articles sourced from prominent databases. The findings revealed a concentration of research influenced by leading brands, with a notable presence in specialized journals dedicated to cosmetic products. While quantitative surveys predominated as the primary research method, the absence of explicit theoretical frameworks suggests a need for further theoretical development tailored to the unique characteristics of organic beauty products. Additionally, the thematic analysis highlighted both progress and existing gaps in understanding sales and distribution strategies, emphasizing the necessity for more comprehensive and theoretically informed research to advance knowledge in this field.